Biological activities of gastropods secretions: snail and slug slime - Muhammad Rashad; Simone Sampò; Amelia Cataldi; Susi Zara (Natural Products and Bioprospecting, 2023)
Abstract Gastropods, a mollusk class including slugs and snails, represent an extraordinarily diverse and ecologically significant group of organisms featuring the largest class of invertebrates. They can be classified as aquatic and terrestrial animals having coiled shells, although some species have reduced or absent shells. Their unique body structure includes a muscular foot for locomotion, a visceral mass containing essential organs, and a distinct head region with sensory organs such as tentacles and eyes. They are used to secrete a complex mixture of glycoproteins, enzymes, peptides, mucus and other bioactive compounds, namely slime, which represents a tool to allow locomotion, protection, and interaction within different habitats. The biological activities of the slime have attracted considerable interest due to their diverse and potentially valuable properties ranging from defense mechanisms to potential therapeutic applications in wound healing, antimicrobial therapy, management of inflammation, and neurological disorders. This review aims at exploring the beneficial effects of snail and slug slime focusing, in particular, on the improvement of the biological processes underlying them. Continued exploration of the intricate components of these slimy secretions promises to discover new bioactive molecules with diverse applications in various scientific and industrial fields. Graphical Abstract